Relating Worlds of Racism Dehumanisation, Belonging, and the Normativity of European Whiteness - Essed, Philomena; Farquharson, Karen; Pillay, Kathryn; White, Elisa Joy.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This international edited collection examines how racism trajectories and manifestations in different locations relate and influence each other. The book unmasks and foregrounds the ways in which notions of European Whiteness have found form in a variety of global contexts that continue to sustain racism as an operational norm resulting in exclusion, violence, human rights violations, isolation and limited full citizenship for individuals who are not racialised as White. The chapters in this book specifically implicate European Whiteness - whether attempting to reflect, negate, or obtain it - in social structures that facilitate and normalise racism. The authors interrogate the dehumanisation of Blackness, arguing that dehumanisation enables the continuation of racism in White dominated societies. As such, the book explores instances of dehumanisation across different contexts, highlighting that although the forms may be locally specific, the outcomes are continually negative for those racialised as Black. The volume is refreshingly extensive in its analyses of racism beyond Europe and the United States, including contributions from Africa, South America and Australia, and illuminates previously unexplored manifestations of racism across the globe. .
Part One: Racism and the Normativity of European Whiteness -- 1. Looking for Race: Pigmented Pasts and Colonial Mentality in "Non-Racial" Africa; Moses E. Ochonu -- 2. Practices "Odious Among the Northern and Western Nations of Europe": Whiteness and Religious Freedom in the United States; Danielle N. Boaz -- 3. The 'Indian' Question: Examining Autochthony, Citizenship, and Belonging in South Africa; Kathryn Pillay -- 4. Don't Know Nothin' 'bout Subsistence. We Gullah! Construction of Self as Indigenous in the Americas; Sharon Y. Fuller -- 5. Race and Racism in Eastern Europe: Becoming White, Becoming Western; Ian Law and Nikolay Zakharov -- 6. Mestizaje: The All-Inclusive Fiction; Linnete Manrique -- 7. Managing Racism on the Field in Australian Junior Sport; Karen Farquharson, Ramón Spaaij, Sean Gorman, Ruth Jeanes, Dean Lusher, Jonathan Magee -- 8. Shifting Racialised Positioning of Polish Migrant Women in Manchester and Barcelona; Alina Rzepnikowska -- Part Two: Racism and the Dehumanisation of the Imagined Black -- 9. Black is Not Beautiful: The German Myth of Race; Susann Therese Samples -- 10. A Different Apartheid: Structural, Legal, and Discursive Foundations for Comparing South Africa and Israel; Jeffrey John Barnes -- 11. Gaza, Black Face and Islamophobia: Intersectionality of Race and Gender in (Counter-) Discourse in the Netherlands; Anne de Jong -- 12. Are You Grime or Part-Time?! Reviewing Race & 'Realness' in Britain's Grime Scene; Monique Charles -- 13. Dis'qualified! Serena Williams and Brittney Griner: Black Female Athletes and the Politics of the Im/possible; Delia D. Douglass -- 14. The Emergence of Race as a Social Category in Northern Europe; Anna Rastas -- 15. Peripheralised in the Periphery: Migration, Deportation, and Detainment in Ireland and Spain; Elisa Joy White -- 16. Blackness and Racial Mixture in Portland, Oregan and Esmeraldas, Ecuador; Ethan Johnson.
Keywords: Race; Social structure; Equality; Culture; Race and Ethnicity Studies; Social Structure; Sociology of Culture